FEATURES OF THE TRANSFORMATION OF POLITICAL AND INSTITUTIONAL COMMUNICATION RELATIONS WITH THE INTERNAL AND EXTERNAL ENVIRONMENT UNDER THE INFLUENCE OF THE DIGITALIZATION PROCESS - Павло ПЕТРОВ (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The rapid development of digital technologies has fundamentally changed political-institutional communication relations, changing the dynamics between internal and external environments. As part of the research, based on classical methodology, a theoretical analysis of the transformation of political-institutional communication relations with the internal and external environment under the influence of the digitalization process is carried out. The study examines the specifics of such transformations in the context of digitalization, emphasizing the institutional challenges for political institutions, internal and external environments, namely, primarily environmental engagement and institutional accountability. As part of the study, the basic characteristics of digital communication were defined, including increased accessibility, real-time interaction and the spread of various information channels. It also highlights issues related to misinformation, polarization and the digital divide that can complicate the relationship between institutions and their constituents. The conclusions state that digitalization is a transformative force in the modern political space, it transforms how political institutions interact with the internal and external environment, as well as how political institutions develop and implement political innovations. While the digitalization process offers significant transformative, innovative opportunities to enhance democratic engagement, digitalization also poses institutional challenges that need to be addressed to ensure that the benefits of digitalization are realized without compromising democratic values. The obtained results emphasize the need for adaptive strategies that use digitalization to strengthen democratic processes while mitigating their negative consequences. This research contributes to understanding the interaction between technology and political communication, offering insights for policymakers and scholars interested in navigating the complexities of the digital age.